(3fgGjI GdEOQGc aj OQGjI GdCadGcs - (3bWH GdOjf eMehO Hf eSYhO GdTjQGRj, bWH GdOjf GdTjQGRj,J (B710 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg aGWQ GdSehGJ ahb GdCQVjf YHQI ddfGXQjf Cf CMQQ dfaSi hdSGFQ GdENhGf ai Yde GdgjFI GdJi aEf HGdSYGOI YGdegG s
(3BNQgG (B:s
(3hYdi gPG jecf ESJNQGL eSGMI CLQGe cd ef GdchGcH hgh YOO CeKGdgG ai Pdc GdLQe hecYH Gdejd hgh GdeQGO hgPG BNQ GdcJGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3YdjgG JhbjY eMeO Hf CSYO GdUOjbi GdOhGfis
(3YhQVJ Ydi GdCUd Gdefbhdg efg s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3Gdadcs